Therapeutic strategy and efficacy evaluation of chronic empyema after total pneumonectomy: individualized analysis of six patients - Lei Wang; Yunjie Lv; Guoxue Zhao; Guangjian Li; Zhongliang He; Yunchao Huang; Guangqiang Zhao (Journal of Cardiothoracic Surgery)
Abstract Background Chronic empyema after total pneumonectomy is a potentially fatal complication.The aim of the study is to explore the treatment strategy and clinical efficacy of chronic empyema after pneumonectomy. Methods A retrospective analysis of 6 patients with chronic empyema after pneumonectomy in our hospital. Utilizing a staged surgical model, the treatment approach involved rib debridement drainage, open-window thoracostomy (OWT), and the application of autologous tissue flaps, including free myocutaneous flap, pedicled muscle flap, and pedicled greater omentum, to effectively eliminate the abscess cavity. Results All patients with empyema were successfully treated after surgery, with follow-up durations ranging from 3 to 29 months and an average of (10.50 ± 9.67) months. Re-examination using chest computed tomography (CT) or magnetic resonance imaging (MRI) revealed that the empyema residual cavity had either completely disappeared or had significantly reduced. Conclusion The treatment of chronic refractory empyema after total pneumonectomy by rib debridement drainage, OWT and autologous tissue flap transplantation has a high cure rate and satisfactory clinical effect.